Brother Bear 2 - Gluck, Benjamin; Dempsey, Patrick, 1966-; Suarez, Jeremy; Moranis, Rick.; Thomas, Dave, 1949-; Moore, Mandy, 1984-; Etheridge, Melissa; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Walt Disney Home Entertainment : Distributed by Excel Home Video, 2006)
The Great Spirits send Kenai, along with Nita, a girl who knew Kenai way back when he wasn't a bear, on a great big, exciting journey to break a pact they made years ago.
Music composer, Melissa Etheridge.
Special features: "Behind the music of 'Brother Bear 2'" bonus video; "Trample off, eh?" game.
Voices: Patrick Dempsey, Jeremy Suarez, Rick Moranis, Dave Thomas, Mandy Moore, Wanda Sykes, Andrea Martin, Catherine O'Hara, Wendie Malick, Kathy Najimy, Michael Clark Duncan, Jim Cummings.
MPAA rating: G.
DVD, region 1, widescreen (1.78:1) presentation; Dolby Digital 5.1 surround.
English, dubbed French or dubbed Spanish dialogue; closed-captioned.
Keywords: Bears -- Juvenile films; Spirits -- Juvenile films; Adventure and adventurers -- Juvenile films; Feature films; Animated films; Children's films; Video recordings for the hearing impaired